The Photorhabdus Virulence Cassettes RRSP-Like Effector Interacts With Cyclin-Dependent Kinase 1 and Causes Mitotic Defects in Mammalian Cells - Wang, Xia; Shen, Jiawei; Jiang, Feng; Jin, Qi (Frontiers in Microbiology, 2020)
The “Photorhabdus virulence cassettes” (PVCs) secreted by Photorhabdus are defined as “extracellular contractile injection systems” (eCISs) and can deliver effectors to eukaryotic hosts for cytotoxicity. Previously, we demonstrated the cryogenic electron microscopy (cryo-EM) structure and assembly process of an intact PVC particle from P. asymbiotica. In this work, we characterized the biological functions of a PVC effector, which is defined as a homologous protein of Ras/Rap1-specific endopeptidase domain (RRSP) in the multifunctional autoprocessing repeats-in-toxin (MARTX) toxin from Vibrio vulnificus. In this work, we found that the RRSP homologous protein (RRSPPa) was associated with inhibition of cell proliferation and increased cell apoptosis and death of HeLa cells. Furthermore, we discovered that RRSPPa disturbed mitotic progression, including the induction of cell cycle alteration, retardation of cell abscission time and regression of the cleavage furrow. In addition, we revealed that RRSPPa could target the cyclin-dependent kinase 1 (CDK1) protein and block activation of CDK1 through inhibition of Thr161 phosphorylation, which partially explained the crucial role of this effector in cell mitosis.